2013
DOI: 10.1111/sms.12068
|View full text |Cite
|
Sign up to set email alerts
|

Motivational and social cognitive predictors of doping intentions in elite sports: An integrated approach

Abstract: Doping use is an important issue in both competitive and non-competitive sports, and poses potentially irreversible health consequences to users. Scholars increasingly call for theory-driven studies on the psychosocial processes underlying doping use that will inform subsequent policy-making and prevention interventions. The aim of the study was to implement an integrative theoretical model to assess the direct and indirect effects of motivational variables, moral orientations, and social cognitions on doping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
107
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 47 publications
14
107
0
4
Order By: Relevance
“…We used self-efficacy to refrain from doping instead of perceived behavioral control as they both reflect efficacy beliefs. Further, past evidence has shown that self-efficacy to refrain from doping is a stronger predictor of doping intentions [16] and, in contrast to perceived behavioral control, a significant predictor of doping intentions in both users and non-users [94]. This model did not fit well [95]:  2 (3) = 288.98, p < 0.001, comparative fit index (CFI) = 0.92, root mean square error of estimation (RMSEA) = 0.14, standardized root mean square residual (SRMR) = 0.04.…”
Section: Path Analyses Of a Theory Of Planned Behavior Modelmentioning
confidence: 93%
“…We used self-efficacy to refrain from doping instead of perceived behavioral control as they both reflect efficacy beliefs. Further, past evidence has shown that self-efficacy to refrain from doping is a stronger predictor of doping intentions [16] and, in contrast to perceived behavioral control, a significant predictor of doping intentions in both users and non-users [94]. This model did not fit well [95]:  2 (3) = 288.98, p < 0.001, comparative fit index (CFI) = 0.92, root mean square error of estimation (RMSEA) = 0.14, standardized root mean square residual (SRMR) = 0.04.…”
Section: Path Analyses Of a Theory Of Planned Behavior Modelmentioning
confidence: 93%
“…Scenarios have been used in previous doping research [13,35] because they do not require athletes to reveal their true behavior and can refer to various doping situations [16]. We based our approach on both the series of scenarios developed by Zelli et al [15] and the items used to measure doping intentions in past research [3,36]. The participating adolescents and young adults read five hypothetical scenarios concerning doping intentions.…”
Section: Doping Intentionsmentioning
confidence: 99%
“…To date, resistive self-regulatory efficacy has been shown to be an indirect predictor of sports cheating variables through moral disengagement in adolescents. In a recent meta-analysis [1], self-regulatory efficacy was a negative predictor of doping intentions [3,5,17] in the sports context. Last, Ring and Kavussanu [16] showed that doping self-regulatory efficacy was associated with doping intentions both directly and indirectly through doping moral disengagement.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations